Sacubitril/valsartan (Entresto) utilisation and prescribing patterns in the context of a reimbursement application system. Issue 2 (12th June 2020) - Kennedy, Cormac; Smith, Amelia; Doran, Stephen; Barry, Michael
Abstract : Aims: Entresto (sacubitril/valsartan) is used to treat symptomatic chronic heart failure with reduced ejection fraction. Given its high potential budget impact, the Health Services Executive introduced a reimbursement application system (RAS) to ensure its appropriate use. The aim of this study was to evaluate the utilisation of Entresto in Ireland and compare patient characteristics to those of the pivotal PARADIGM‐HF trial. Methods: We used dispensed claims data from the Primary Care Reimbursement Services, clinical data obtained from the RAS, and data from published studies of Entresto utilisation. Differences in the baseline characteristics in the study populations vs the Entresto arm of the PARADIGM‐HF trial were analysed. We also investigated cardiovascular medication use in the 6 months pre‐ and post‐Entresto initiation. Results: In 2018, there were 1043 individuals receiving Entresto, corresponding to an expenditure of €1.2 million. Patients prescribed Entresto in Ireland were older, had lower left ventricular ejection fraction and were more symptomatic than those in the PARADIGM‐HF trial. Irish patient characteristics were reflective of Entresto‐treated populations in other real‐world studies. More than 63% of patients were commenced on the lowest Entresto dose. Entresto initiation was associated with a reduction in the use of other medications for heart failure. Conclusion: The utilisation of Entresto has been steadily increasing in Ireland since its reimbursement approval. The expenditure in the first year was substantially lower than predicted, and the RAS is an example of how health technology management can facilitate appropriate and cost‐effective use of medicines.